Cho a>0,b>0 $\frac{1}{a}+$ $\frac{1}{b}=1$ CMR $\sqrt{a+b}=$$\sqrt{a-1}+$ $\sqrt{b-1}$

Question

Cho a>0,b>0
$\frac{1}{a}+$ $\frac{1}{b}=1$ CMR $\sqrt{a+b}=$$\sqrt{a-1}+$ $\sqrt{b-1}$

in progress 0
Mít Mít 8 tháng 2020-10-18T02:34:19+00:00 2 Answers 85 views 0

Answers ( )

  1. Đáp án:

     

    Giải thích các bước giải:

     $\frac{1}{a}$ + $\frac{1}{b}$ = 1 

    ⇒ $\frac{1}{a}$ = 1 – $\frac{1}{b}$ = $\frac{b-1}{b}$ 

    ⇒a = $\frac{b}{b-1}$ 

    Ta có :

    $\sqrt[]{a+b}$ = $\sqrt[]{b+\frac{b}{b-1}}$ = $\frac{b}{ \sqrt[]{b-1} }$ ( 1 )

    Mặt khác :

    $\sqrt[]{a-1}$ + $\sqrt[]{b-1}$ = $\sqrt[]{\frac{b}{ \sqrt[]{b-1} }-1}$ + $\sqrt[]{b-1}$ = $\frac{1}{ \sqrt[]{b-1}}$ + $\sqrt[]{b-1}$ = $\frac{b}{ \sqrt[]{b-1} }$     ( 2 )

    Từ ( 1 ) và ( 2 ) ⇒ đpcm 

  2. Đáp án:

    Giải thích các bước giải:

    $\dfrac{1}{a}+\dfrac{1}{b}=1$

    $⇔ \dfrac{a+b}{ab}=1$

    $⇔ a+b=ab$

    $\text{Mặt khác:}$ $\sqrt{a+b}=\sqrt{a-1}+\sqrt{b-1}$ $(1)$

    $\text{ĐKXĐ: $a \geq 1$; $b \geq 1$}$

    $⇔ a+b=a-1+2\sqrt{(a-1)(b-1)}+b-1$

    $⇔ a+b-a-b+2=2\sqrt{(a-1)(b-1)}$

    $⇔ \sqrt{(a-1)(b-1)}=1$

    $⇔ ab-a-b+1=1$

    $⇔ ab-(a+b)=0$

    $⇔ ab-ab=0$

    $⇔ 0=0$ $\text{(luôn đúng)}$

    $\text{⇒ (1) được chứng minh}$

Leave an answer

Browse

2x(x - 3) + 5(x - 3) = 0 (x>0) , x = ? ( )